Meta-analysis of magnetic resonance imaging studies of the corpus callosum in schizophrenia. - Arnone, D; McIntosh, A; Tan, G; Ebmeier, K (2008)
The corpus callosum plays a pivotal role in inter-hemispheric transfer and integration of information. Magnetic resonance studies have reported callosal abnormalities in schizophrenia but findings have been inconsistent. Uncertainty has persisted despite a meta-analytic evaluation of this structure several years ago. We set out to perform a further meta-analysis with the addition of the numerous reports published on the subject to test the hypothesis that the corpus callosum is abnormal in schizophrenia.A systematic search was carried out to identify suitable magnetic resonance studies which reported callosal areas in schizophrenia compared to controls. Results from the retrieved studies were compared in a meta-analysis whilst the influence of biological and clinical variables on effect size was ascertained with meta-regression analysis.Twenty-eight studies were identified. Corpus callosum area was reduced in schizophrenia in comparison to healthy volunteers. This effect was larger in first episode patients. Similarly, heterogeneity detected among the studies was associated with course of illness indicating that chronic subjects with schizophrenia showed larger callosal areas. There was no evidence of publication bias.This study confirms the presence of reduced callosal areas in schizophrenia. The effect is of a larger magnitude at first presentation and less so in subjects with a chronic course generally medicated with antipsychotics.